Odontogenic Orocutaneous Fistula: Diagnosis and Management-Review for Dentists - Hussain A, Shmakhi Sharifah; Mahdi Zahran Mohammed A; Tahreer Mohammed Naser Hefzy; Alhazmi Amnah Ahmed; Fadiyah Nasser Alharbi; Layla Ahmad Awaji; Fatimah Mohammed Nasir Alhazmi; Afaf Murajjiha Almutairi; Haya Soud Elenazi; Reem Mohammed Kinani; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Odontogenic orocutaneous fistula (OCF) is an uncommon pathological communication between the oral cavity and skin, often misdiagnosed due to its atypical presentation. Chronic dental infections are the predominant cause, though trauma, osteomyelitis, medication-related osteonecrosis, and neoplasia also contribute. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review the etiology, diagnostic challenges, and management strategies for odontogenic OCF, emphasizing its clinical significance for dental practitioners. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature review was conducted, analyzing epidemiology, pathophysiology, diagnostic modalities, and treatment approaches. Key studies and case reports were synthesized to highlight common pitfalls and best practices. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Odontogenic sources account for most OCF cases, typically arising from untreated pulpal necrosis and periapical infection. Misdiagnosis is frequent, with lesions often mistaken for dermatologic conditions such as cysts or granulomas. Radiographic tracing with gutta-percha and pulp vitality testing are essential for accurate localization. Endodontic therapy or extraction of the causative tooth leads to spontaneous closure in most cases, while adjunctive measures like vacuum-assisted closure may be required for complex defects. Prognosis is excellent when timely dental intervention occurs, though residual scarring may persist. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Early recognition of odontogenic origin is critical to prevent unnecessary interventions and aesthetic complications. Interdisciplinary collaboration between dermatology, surgery, and dentistry enhances diagnostic accuracy and patient outcomes.